2021
DOI: 10.1039/d1fo00658d
|View full text |Cite
|
Sign up to set email alerts
|

Human milk oligosaccharide 2′-fucosyllactose supplementation improves gut barrier function and signaling in the vagal afferent pathway in mice

Abstract: 2’-Fucosyllactose (2’-FL), a predominant human milk oligosaccharide, attenuates HF diet-induced metabolic and intestinal barrier impairment, improves gut hormone resistance, and alters the intestinal microbiota and microbiota-derived metabolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 60 publications
4
22
0
Order By: Relevance
“…The absence of an effect on body weight and food intake is in line with short-term studies (6-8 weeks) that used comparably low doses of 2 -FL (1 and 2% w/v) as herein (2.5% w/w) (33). In these short-term studies only the higher doses of 2 -FL (5 and 10% w/v) decreased body weight, which was also associated with a lowering of caloric intake (33,34). In line with our findings, no major effect on plasma lipids was observed in a meta-analysis of other types of prebiotic treatments in ultrasound-or biopsy-confirmed NAFLD patients (6).…”
Section: Discussionsupporting
confidence: 73%
“…The absence of an effect on body weight and food intake is in line with short-term studies (6-8 weeks) that used comparably low doses of 2 -FL (1 and 2% w/v) as herein (2.5% w/w) (33). In these short-term studies only the higher doses of 2 -FL (5 and 10% w/v) decreased body weight, which was also associated with a lowering of caloric intake (33,34). In line with our findings, no major effect on plasma lipids was observed in a meta-analysis of other types of prebiotic treatments in ultrasound-or biopsy-confirmed NAFLD patients (6).…”
Section: Discussionsupporting
confidence: 73%
“…HMOs are complex glycans [ 5 ] that withstand digestion of the upper gastrointestinal tract [ 6 , 7 ] to act as a prebiotic in the lower gastrointestinal tract [ 11 , 12 ], with physiological benefits for the infant [ 1 , 2 , 3 , 34 ]. HMO are proposed to influence intestinal development [ 8 , 9 , 10 ], as well as microbiota composition by promoting growth of Bifidobacterium species, including B. infantis [ 11 , 12 , 13 ]. Infant formulas that contain prebiotics, such as galactooligosaccharides (GOS) and fructooligosaccharides, support Bifidobacterium growth are currently commercially available [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that 2’-FL and Bi-26 alone or in combination would be well tolerated and support normal piglet growth, and aimed to investigate any synergy between 2’-FL and Bi-26. Based on previous evidence [ 8 , 9 , 10 ], we further hypothesized that 2’-FL would promote intestinal development in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumption of HMOs during early-life, specifically 2′-FL, alters various modulators of the gut-brain axis, including lowering pro-inflammatory immune responses, increasing bifidobacteria abundance in the gut, and improving the gut barrier integrity and vagal afferent signaling ( Goehring et al, 2016 ; Cerdo et al, 2017 ; Berger B. et al, 2020 ; Lee et al, 2021 ). Additionally, numerous animal and clinical studies have demonstrated the long-term beneficial effects of 2′-FL consumption during early-life in terms of cognitive development ( Oliveros et al, 2016 ; Berger P. K. et al, 2020 ) and potential mechanisms for brain structural changes ( Vázquez et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%